Implementation of the Labor-Intensive Paving Block Production Program Policy for Poor Families in Tambaksari District, Surabaya City - Edista Indiswari Artamefia; Shelly Ayu Permata Putri; Al Viana Amelia Pratiwi; Diana Putri Wahyudi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The Labor-Intensive Program is a community empowerment strategy that focuses on creating temporary jobs through productive activities based on local resources. This program aims to reduce unemployment and directly increase the income of poor communities. In Surabaya City, specifically in Tambaksari District, the labor-intensive program is implemented in the form of paving block production involving underprivileged communities as labor. This study aims to analyze the implementation of the Labor-Intensive Program policy for paving block production using George C. Edward III's policy implementation theory, which includes aspects of communication, resources, disposition, and bureaucratic structure. The approach used is descriptive qualitative with data collection through interviews, observation, and documentation. The results of the study indicate that the program has succeeded in creating jobs and increasing community income, although there are still obstacles in terms of communication continuity, limited human resources and production equipment, and inconsistencies in some implementation with applicable SOPs. The disposition of implementers and flexibility in the bureaucratic structure are key factors in maintaining the sustainability and effectiveness of the program. These findings are expected to contribute to the development of more sustainable and inclusive community empowerment policies. Keywords: Labor Intensive, Poverty, Policy Implementation, Paving Blocks, Surabaya.